A suspected virus infection of the oral mucosa in Swedish reindeer (Rangifer tarandus L) - Rehbinder, C.; Nordkvist, M.; Moreno, J.W.; Siddiqui, Islam-ud-din (Rangifer, 1985)
During the winter 1980 reindeer herds in the Tornedalen area, along the Finnish border, were hit by grazing difficulties. Thus minor parts of the reindeer her*ds in this area were given supplementary feed in pens. Some of the supplementary fed animals were taken ill and some deaths occurred. According to the owners sick animals showed loss of appetite and signs of fever. A total of 8 carcasses were necropsied at The National Veterinary Institute. In 5 of these cases oral lesions were observed. The histological investigation of the oral mucosa revealed intracytoplasmic inclusion bodies, inter- and intracellular oedema and vesicle formation. An electron-microscopical study of 2 of the cases confirmed the histological findings. At the bacteriological investigations Coli, ß-haemolyzing streptococci, Conrynebacterium pyogenes and Fusobacterium necrophorum could be indentified. The found bacteria were all considered secondary invaders. Serological samples from four affected reindeer flocks were tested for antibodies against BVD-, P13 and IBR-virus as well as Chlamydia. A few samples showed low positive titres for agents tested but for BVDV. The result of the investigation indicates that a still unidentified virus could be the primary cause of this enzootically appearing disease of the oral mucosa in reindeer.Misstanke om virusinfektion i munnslemhinnan på svensk ren.Abstract in Swedish / Sammanfattning: Under vintern 1980 drabbades renhjordar i Tornedalsområdet av betessvårigheter. Av denna anledning fördes mindre flockar, ur hjordarna, till inhägnader och tillskottsutfodrades. En del av de tillskottsutfodrade djuren insjuknade och dödsfall inträffade. Enligt djurägarna förlorade de sjuka djuren aptiten och uppvisade tecken på feber. Av de döda renarna erhölls åtta fôr obduktion vid Statens Veterinärmedicinska anstalt. Hos fem av de obducerade renarna forelåg skador i munhålan. Vid histologisk undersokning av munslemhinnan påvisades intracytoplasmatiska inklusionskroppar, inter- och intracellulärt ödem och vesikelbildningar. Elektronmikroskopisk undersokning av två av fallen konfirmerade de histologiska undersökningarna. Vid de bakteriologiska undersökningarna påvisades våxt av kolibakterier, ß-hemolyserande streptokocker, Corynebacterium pyogenes och Fusobacterium necrophorum. I samtliga fall betraktades dessa som sekundårinfektio-ner. Serologiska undersökningar företogs, i fyra flockar dår dödsfall förekommit, avseende forekomst av antikroppar emot BVD-virus, Pi3 och IBR-virus samt Chlamydia. Ett mindre antal prover uppvisade positiva titrar fôr de undersökta agens utom vad avser BVD. Resultaten av undersökningarna indikerar att ett annu ej identifierat virus kan vara primärorsak till de enzootiskt upptrådande utbrotten av sjukliga förändringar i munhålen hos ren.
Keywords: reindeer; oral lesions; virus; necrobacillosis; oral mucosa